In-hospital bleeding occurring while treating ST-segment elevation myocardial infarction during the COVID-19 pandemic: STEMI during the COVID-19 pandemic : Bolnišnične krvavitve med zdravljenjem akutnih miokardnih infarktov z dvigom veznice ST med pandemijo Covid-19: STEMI bolniki med pandemijo Covid-19 - Kvartuh, Matej; Lah, Domen; Marinšek, Martin; Šuran, David; Sinkovič, Andreja (Acta Medico-Biotechnica, 2023)
Pursose. Our purpose was to evaluate less well known factors and outcome associated to bleeding in STEMI patients after primary PCI and concomitant antithrombotic therapy during Covid-19 pandemic.Methods. This was a retrospective, observational study of the prevalence and factors associated to hospital bleeding in 317 STEMI patients (74.8% men, mean age 65.7±11.9 years) and of the impact of bleeding on 30-day and 6-month survival in STEMI patients during the Covid-19 pandemic from January-October 2021. The leading reperfusion strategy was primary PCI; we registered all significant bleeding events. Results: Concomittant Covid-19 was observed in 3.2% of STEMI patients. Primary PCI was performed in 94.3% of all cases, but only in 17% within the first 3 hours of chest pain. Bleeding was observed in 11.4% of all STEMI patients and was associated significantly with out-of-hospital cardiac arrests (OHCA), hospital complications and mortality. In bleeding and nonbleeding patients the prevalence of age, sex, comorbidities, Covid-19 cases, the use and start of primary PCI was similar.Conclusions: The prevalence of hospital bleeding in treatment of STEMI patients during Covid-19 pandemic was 11.4% and was associated significantly to OHCA, hospital complications and early mortality of STEMI patients.
Keywords: COVID-19 pandemic, ST-elevation myocardial infarction, bleeding, mortality, hospital complications